2018
DOI: 10.33314/jnhrc.v16i2.896
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Burden in Caregivers of Children with Autism Spectrum Disorder

Abstract: Background: Autism Spectrum Disorder is a lifelong developmental disorder that affects children and results in deficit in social interaction, communication and display of unusual pattern of behavior. Though caregiving is a normal parental duty, providing intensive care to a child with long-term problem is burdensome and impacts both physical and mental health of caregivers. The aim of this study was to obtain a picture of burden among caregivers raising children with Autism Spectrum Disorder.Methods: We conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
1
8
2
Order By: Relevance
“…Interestingly, most caregivers claimed not to have any health problems and considered their health status to be good/stable. However, this differs from the study presented by Pandey and Sharma [26], which concluded that providing 24/7 care to a PSN for many years considerably affects the caregiver's physical health. Patel et al [9] added that a general health status can be impaired mainly in low-income populations.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Interestingly, most caregivers claimed not to have any health problems and considered their health status to be good/stable. However, this differs from the study presented by Pandey and Sharma [26], which concluded that providing 24/7 care to a PSN for many years considerably affects the caregiver's physical health. Patel et al [9] added that a general health status can be impaired mainly in low-income populations.…”
Section: Discussioncontrasting
confidence: 94%
“…The authors stated that these caregivers could be reliably identified by administering the ZBI scale alone and their data confirm the anxiety-related overload shown in other studies [21,23]. The moderate overload found seems consistent with the findings of several other studies [26][27][28], although Moreira et al [29] and Estrada-Hernandez [23] demonstrated more intense overload. Despite a moderate burden being identified in our study, the caregivers did not declare substantially elevated anxiety; on the contrary, they showed general compliance and satisfaction with access to dental care services dedicated to PSN.…”
Section: Discussionsupporting
confidence: 80%
“…A total score was calculated by the sum of all the item scores and high scores indicate a higher level of burden. Scores were interpreted as 0-20: no burden, 21-40: mild to moderate burden, 41-60: moderate to severe burden and 61-88 severe burden according to Modified Zarit Burden Interview Scale [4].…”
Section: Study Design and Settingmentioning
confidence: 99%
“…The caretakers had a considerable source of income from their private or governmental jobs while most mothers were homemakers. A similar study conducted in Nepal showed that employment has no significant association with the caregiver’s burden 23 .…”
Section: Discussionmentioning
confidence: 92%